THE IMPLEMENTATION OF LC7E MODEL ON SCIENCE PROCESS SKILLS TO FOURTH GRADE OF SD NEGERI 2 KEBUMEN - Astika Krisnawati; Kartika Chrysti Suryandari; Muhamad Chamdani (Universitas Sebelas Maret, 2021)
The study aimed to determine the effectiveness LC7E (Learning Cycle 7E) model on science process skills to fourth grade students of SD Negeri 2 Kebumen to the theme of animal life cycle and environmental protection. It was collaborative classroom action research (CAR) carried out in one cycle. It consisted of planning, implementation, observation, and reflection. The subjects were 18 fourth grade students of SD Negeri 2 Kebumen. The data were analyzed by qualitative descriptive. It concludes that Learning Cycle 7E (LC7E) model improves science process skills and natural science learning outcomes of fourth grade students. The increasing of science process skills was 37%, students learning outcome was 33.89%, and NGain was 57.14%.